2009
DOI: 10.1016/j.rmed.2009.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma TGF-β1 levels in patients with chronic obstructive pulmonary disease

Abstract: The findings of elevated plasma TGF-beta(1) levels in patients with COPD suggest that TGF-beta(1) may play a role in COPD pathogenesis. The C-509T and T869C functional polymorphisms of TGF-beta(1) gene do not represent a genetic predisposition to COPD susceptibility in Hong Kong Chinese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 36 publications
2
46
0
3
Order By: Relevance
“…As described previously, TGF-β1 is elevated in serum from COPD patients [53], which could lead to increased numbers of Th17 cells. Serum and sputum levels of IL-6 are increased during periods of exacerbations in COPD [84], again potentially leading to increased numbers of Th17 cells.…”
Section: Control Of Differentiationmentioning
confidence: 60%
See 1 more Smart Citation
“…As described previously, TGF-β1 is elevated in serum from COPD patients [53], which could lead to increased numbers of Th17 cells. Serum and sputum levels of IL-6 are increased during periods of exacerbations in COPD [84], again potentially leading to increased numbers of Th17 cells.…”
Section: Control Of Differentiationmentioning
confidence: 60%
“…IL-2-deficient mice have a reduced number of nT reg -cells, indicating the importance in T regcell proliferation [52]. Increased levels of TGF-β1 in serum in patients with COPD compared with healthy controls has been found [53]. In addition, IL-2 levels are higher in patients with stable COPD [54] compared with those who exhibit a rapid decline in lung function.…”
Section: Control Of Differentiationmentioning
confidence: 99%
“…It has reported TGF-β1 elevated in the plasma of COPD patients 23,24) and increased the release of active TGF-β1 induced by cigarette smoke in rat tracheal explant. 25) We found in this study that enhanced TGF-β1 expression correlated with the increase in airway wall thickness and collagen deposition and that the elevation of TGF-β1 in the mRNA and protein level was significantly inhibited in COPD rats after HSYA treatment.…”
Section: Disscusionmentioning
confidence: 99%
“…A genome-wide linkage analysis in the Boston Early-Onset COPD study suggested that SERPINE2 may be associated with the COPD-related phenotypes (Palmer et al, 2003;Silverman et al, 2002). Similarly, the association analysis of the family-based data showed significant association of multiple SERPINE2 single nucleotide polymorphisms (SNPs) with COPD related-phenotypes, which was confirmed by Mak et al, 2009;Su et al, 2005) than in European (van Diemen et al, 2010;Wu et al, 2004). Given the large differences in genetic background of Asians and Europeans (Li et al, 2008;Zhao and Lee, 1989), it is important to provide further evidences related to these distinct populations to detect the complexity of COPD.…”
Section: Introductionmentioning
confidence: 84%